Indoles Derived From Glucobrassicin: Cancer Chemoprevention by Indole-3-Carbinol and 3,3'-Diindolylmethane - Williams, David E. (Frontiers in Nutrition, 2021)
Hydrolysis of glucobrassicin by plant or bacterial myrosinase produces multiple indoles predominantly indole-3-carbinol (I3C). I3C and its major in vivo product, 3,3’-diindolylmethane (DIM), are effective cancer chemopreventive agents in pre-clinical models and show promise in clinical trials. The pharmacokinetics/pharmacodynamics of DIM have been studied in both rodents and humans and urinary DIM is a proposed biomarker of dietary intake of cruciferous vegetables. Recent clinical studies at Oregon State University show surprisingly robust metabolism of DIM in vivo with mono- and di-hydroxylation followed by conjugation with sulfate or glucuronic acid. DIM has multiple mechanisms of action, the most well-characterized is modulation of aryl hydrocarbon receptor (AHR) signaling. In rainbow trout dose-dependent cancer chemoprevention by dietary I3C is achieved when given prior to or concurrent with aflatoxin B1, polycyclic aromatic hydrocarbons, nitrosamines or direct acting carcinogens such as N-methyl-N’-nitro-nitrosoguanidine. Feeding pregnant mice I3C inhibits transplacental carcinogenesis. In humans much of the focus has been on chemoprevention of breast and prostate cancer. Alteration of cytochrome P450-dependent estrogen metabolism is hypothesized to be an important driver of DIM-dependent breast cancer prevention. The few studies done to date comparing glucobrassicin-rich crucifers such as Brussels sprouts with I3C/DIM supplements have shown the greater impact of the latter is due to dose. Daily ingestion of kg quantities of Brussels sprouts is required to produce in vivo levels of DIM achievable by supplementation. Sulforaphane from glucoraphanin can act synergistically with glucobrassicin-derived DIM and this may lead to opportunities for combinatorial approaches (supplement and food-based) in the clinic.